Literature and ageing - Barry, Elizabeth, 1972- (Essays and studies (London, England : 1950), 2020)
New approaches to the topics of old age and becoming old depicted in a range of texts from modern literature. The central focus of this book is the experience of growing old as represented in literature from the mid-nineteenth century to the present day: an experience shaped by changes in longevity, a new science of senescence, the availability of state pensions, and other phenomena of recent history. The collection considers the increasing prominence of stories of ageing, challenging the idea that old age is an uneventful time outside of the parameters of literary narrative. Instead, age increasingly is the story. As the older population swells, political crises are construed as the old stealing from the young, and the rights of older people are sacrificed to the economics of care, it becomes ever more important to think about and question, as literature does, the symbolic aspects of ageing - the cultural imaginary that determines the way that society sees old age. The work in this volume explores age stories in relation to futurity, precarity and climate change. It brings to light narratives of resistance to colonial imperialism and reproductive futurism framed in terms of age; and tests the lived experience of growing old and the challenge it offers to individualistic conceptions of selfhood, work and care. The literary works examined - hailing from England, North America, Japan and the Caribbean, and including texts by Margaret Drabble, Samuel Beckett and Matthew Thomas - ask how we feel about ageing - so often the determinant of how we think about it.